2007
DOI: 10.1002/j.1556-6678.2007.tb00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Autism: Implications for Counselors

Abstract: The author reviews an article (L. C. Eaves & H. H. Ho, 2004) published in the Journal of Autism and Developmental Disorders that discussed screening tools and diagnostic assessments used to identify autism in 2‐year‐olds as well as a follow‐up study 2½ years later. The author also provides a discussion of the impact of receiving this diagnosis on families and roles for counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…There have been few articles published in counselor education journals discussing the population of clients with autism or their families. One study concluded that there was a need for more research understanding the roles of counselors working with clients who have ASD and their families (Layne, 2007). In reality, many counselors will find themselves working with parents who have a child with autism or their child diagnosed with ASD.…”
Section: Counselor Education In Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few articles published in counselor education journals discussing the population of clients with autism or their families. One study concluded that there was a need for more research understanding the roles of counselors working with clients who have ASD and their families (Layne, 2007). In reality, many counselors will find themselves working with parents who have a child with autism or their child diagnosed with ASD.…”
Section: Counselor Education In Autismmentioning
confidence: 99%
“…The roles that counselors have in working with this population may be inconclusive, although there are responsibilities in advocacy and support that are needed. Supports may lie in advocacy for increased state and federal funding to support early intervention and for counseling services for children with autism and their families (Layne, 2007).…”
Section: Ethical and Multicultural Issuesmentioning
confidence: 99%
“…Families who have young children at risk for ASD have initial experiences that may differ from other families who have children with disabilities. Families who have young children at risk for ASD are frequently unaware of this disability until the child is approximately 2 years of age, while other families are aware of a disability much sooner (Layne 2007).This timing of the diagnosis may impact family adjustment, service needs and entry into the service delivery system (Nelson 2002;Hiebert-Murphy et al 2008).Therefore, it is important to learn how specific practices impact families who have a young child with ASD.…”
Section: O N C L U S I O Nmentioning
confidence: 99%
“…As the prevalence of ASD increases, so does the need for appropriate interventions to help curtail the associated impairments resulting from the disorder (Krell & Perusse, ; Layne, ). Historical approaches to treating autistic symptoms have primarily included behavioral interventions that focus on the child's deficits.…”
mentioning
confidence: 99%
“…Although researchers have demonstrated that behavioral strategies are effective in building specific skills (see Reichow, Doehring, Cicchetti, & Volkmar, ), there remains a need to address the interpersonal dynamics and struggles of children with ASD. Some experts in the field of ASD have proposed play‐based interventions for working with children with ASD (Gallo‐Lopez & Rubin, ; Greenspan & Wieder, ; Layne, ), providing support for using play therapy as a method of treatment.…”
mentioning
confidence: 99%